Professional Learning from Classroom-Based Inquiries - Jhagroo, Jyoti Rookshana; Stringer, Patricia Martha (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book provides authentic practice-based inquiries by pre-service teachers. Their reflective narratives showcase their individual inquiries as they navigated their self-chosen professional learning journeys through the teaching as inquiry framework. The narratives advance what it means to be a reflective practitioner in practice and highlight necessary dispositional skill sets to attain valuable professional learning through inquiry. Through an inquiry stance, pre-service teachers are liberated from being knowledge consumers to local knowledge producers relevant to their practice. The dissonance this shift creates, negates the 'comfortable doing' of teaching to make the act of teaching authentic, relevant, and powerful. .
Incorporating pretend play to increase engagement and motivation for young learners who are reluctant to explore beyond their comfort zones -- Using Music as a Tool to Develop Growth Mind-set Learning Habits -- Zines and literacy - Enhancing boys' engagement with literacy lessons -- How can I reimagine my practice so that I teach 'big ideas' rather than subject-specific content? -- Using the arts in the classroom to promote soft skills -- Using technology to support my teaching of mathematics in a play-based learning environment -- Integration of Visual Arts and Social Studies exploring propaganda: promoting learners to be critical thinkers taking social action -- Integrating music/song lyrics into literacy to engage reluctant learners to develop critical literacy and awareness around global issues -- Does putting play at the centre of the curriculum aid the learning of oral language? -- Feeling in Silence: Using Drama to promote the Language Acquisition and Wellbeing of English as an Additional Language (EAL) learners.
Keywords: Teachers -- Training of; Professional education; Vocational education; Education; Children; Teaching and Teacher Education; Professional and Vocational Education; Childhood Education